Building a diagnostic ontology of social-ecological systems - Ulrich J Frey; Michael Cox (International Journal of the Commons, 2015)
This article argues that research on social-ecological systems could profit from the use of ontologies. Ontologies, i.e. formalized conceptualisations of a domain in a computer-readable format, allow making progress in different areas. In particular, a diagnostic approach would be facilitated, in turn addressing the complexity problem (analysing the complexity of social-ecological systems adequately), the panacea problem (the overreliance on simplistic policy prescriptions that do not account for this complexity) and the scatter problem (lack of integration of many research findings into a cohesive set of theoretical statements). Ontologies offer several advantages, e.g. they structure and formalize domains, unify knowledge, decrease terminological confusion, reduce incomparability, reduce redundancy of efforts and allow automated reasoning. We demonstrate the practical use of ontologies by converting the SES framework into an ontology. This leads to several suggestions on how to improve the framework.